Intention of Bank Customers on the usage of Fintech payment apps with moderating effect on Brand Image of Banks (MSW Management Journal, 2026)
Financial technology's (Fintech) explosive expansion has drastically changed banking practices and consumer relations, particularly in emerging markets like India. In particular, brand image is examined as a moderating factor in this study's investigation of the factors influencing bank customers' inclination to use Fintech payment services. This study integrates constructs like Performance Expectancy, Effort Expectancy, Social Influence, Relative Advantage, and Green Technology to investigate their effects on user intention, drawing on the Unified Theory of Acceptance and Use of Technology (UTAUT) and Diffusion of Innovation (DOI) models. Using structural equation modeling (SEM) to examine survey responses from Indian bank clients, the study finds that all constructs—aside from green technology—have a substantial impact on usage intention. Brand image also acts as a partial mediator in the interaction between user intention and a number of constructs. The findings provide useful information for banks and governments to improve customer engagement, digital service uptake, and sustainability integration. They also emphasize the significance of perceived value, social impact, and technological ease in the use of Fintech services by customers. This study offers a fundamental framework for comprehending the acceptance of Fintech and guides the strategic development of digital banking ecosystems.